2014
DOI: 10.6090/jarq.48.271
|View full text |Cite
|
Sign up to set email alerts
|

A Research Strategy to Understand the Mechanisms that Govern Flower Color Pattern Formation

Abstract: The coloration pattern of flower tissue affects the commercial potential of floricultural plants and is also a subject of fundamental biological interest. Transposon insertion or excision and post-transcriptional gene-silencing are well-studied mechanisms involved when flower color patterns form. In this paper, I present a research strategy to understand the mechanisms that govern the formation of flower color patterns. First, I discuss the significance of flower color pattern-formation research and then go on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The change of ower color area by virus. The well-known example is Tulipa virus which affect or induce the patterns of ower pigmentation (Nakayama, 2014). It indicated that a viral protein act regulating factor for ower pigmentation.…”
Section: Others Owersmentioning
confidence: 99%
“…The change of ower color area by virus. The well-known example is Tulipa virus which affect or induce the patterns of ower pigmentation (Nakayama, 2014). It indicated that a viral protein act regulating factor for ower pigmentation.…”
Section: Others Owersmentioning
confidence: 99%
“…The color patterns create major variations in flower appearance and often enhance the ornamental value of flowers. Consequently, the exploration of the underlying mechanisms involved in the development of anthocyanin color patterns could facilitate the breeding of floricultural crops (Nakayama, 2014). Mechanisms of development of anthocyanin color patterns have been reported in some plant species, mainly model plants (Davies et al, 2012;Glover et al, 2013;Albert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%